Artificial orchid online boutique system / Wan Nur Izati Wan Mansor - Wan Mansor, Wan Nur Izati (2020)
This project is a web based system that focus on flower store for both customer and seller. This system only uses web based for both sellers and buyers. Web based system is for seller who are responsible to update product and also receive order from customers. While for customers they can register their account and make a purchase. Following new trend in our country, everything are on fingers. Hence, web based are for them. This system only can be used by customers who has been register their account in system. From the account, they can purchase any item with variable quantity. Adding to cart their wish list and finally make a payment. After the transaction , the system will produced transaction receipt.